Sistem Komputer Sistem Monitoring Suhu dan Tingkat Kekotoran Pada Air Conditioner (AC) Indoor Menggunakan Teknik Simplex Berbasis Mikrokontroler : Sistem Monitoring Suhu dan Tingkat Kekotoran Pada Air Conditioner (AC) Indoor Menggunakan Teknik Simplex Berbasis Mikrokontroler - Hamjah Arahman; Hirzi, M. Fakhrul; Sari Nasution, Guslila; Chairu Sabila, Puji (Jurnal Teknologi Sistem Informasi dan Sistem Komputer TGD, 2024)
Air Conditioner or what is usually called AC is a room temperature cooling device which is usually placed in the upper corner of the room ceiling or in the corner of the room, which is sometimes not maintained and cannot be reached by the room owner. Almost all companies or large-scale businesses use Air Conditioning (AC) to create comfortable conditions so that all employees can work more optimally. However, this cannot be fully implemented because there are more units in a company than there are technicians employed by that company. Due to conditions like this, an idea was created that would make the work of technicians, especially AC technicians, in a company easier, a system that would be able to determine the condition. The latest Air Conditioner unit uses the Simplex technique and a medium distance signal, namely Microcontroller-based Bluetooth. Equipment that will be placed in every Air Conditioner (AC) unit in every air-conditioned room in a company